The parts of the building: Meronymy in the discourse of construction engineering - Orna Montesinos, Concha (Estudios Ingleses de la Universidad Complutense, 2010)
Drawing on the assumption that professional practices as well as their writing practices condition the lexical choices of the construction engineering community, this paper aims at exploring the role of the semantic relation of meronymy (the part-whole relationship) in the discourse of the specialized textbooks of the discipline. The goal is to reach a wider understanding of the ontological meaning encapsulated in the concept building. For the semantic analysis of the meronyms of the noun building, the Construction Engineering Corpus (of approximately one million words) is contrasted with the WordNet lexical ontology in order to explore which parts of the building are relevant for this community. The analysis shows that meronyms fulfill a dual role in discourse, as lexical items on the one hand and as discourse organizers on the other. This duality is corroborated by the textual and contextual analysis of these meronyms in the some of the basic rhetorical techniques of specialized description, definition and classification; these closely connected to the instructional purpose of the construction engineering specialized textbook genre.